1978
DOI: 10.1111/j.1476-5381.1978.tb08445.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement by Oxotremorine of Acetylcholine Release From the Rat Phrenic Nerve

Abstract: Oxotremorine (10.5 μM) produced a paralytic effect on twitch responses of rat diaphragm in vitro to direct and indirect stimulation. The paralytic effect of oxotremorine was absent when the diaphragm was stimulated directly in the presence of hemicholinium‐3 (0.42 mM), at a time when twitch responses to indirect stimulation ceased completely. Oxotremorine, at two different pharmacologically active doses, strikingly increased the resting as well as electrically evoked release of acetylcholine into the bathing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
0

Year Published

1980
1980
1990
1990

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…The type of cholinoceptor sites involved in the feedback regulation however, is controversial. Muscarinic inhibitory (Duncan & Publicover, 1979;Michaelson et al, 1979;Abbs & Joseph, 1981;Somogyi et al, 1987) and excitatory (Das et al, 1978;Wali et al, 1987;Wessler et al, 1987) prejunctional cholinoceptors have been reported at vertebrate neuromuscular junctions and in the Torpedo electric organ. In the presence of tubocurarine, a frequency-dependent decrease of evoked ACh release was obtained which suggested the presence of nicotinic prejunctional cholinoceptors mediating a positive feedback control of evoked transmitter release (Glavinovic, 1979a;Magleby et al, 1981;Wessler et al, 1986;Matzner et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The type of cholinoceptor sites involved in the feedback regulation however, is controversial. Muscarinic inhibitory (Duncan & Publicover, 1979;Michaelson et al, 1979;Abbs & Joseph, 1981;Somogyi et al, 1987) and excitatory (Das et al, 1978;Wali et al, 1987;Wessler et al, 1987) prejunctional cholinoceptors have been reported at vertebrate neuromuscular junctions and in the Torpedo electric organ. In the presence of tubocurarine, a frequency-dependent decrease of evoked ACh release was obtained which suggested the presence of nicotinic prejunctional cholinoceptors mediating a positive feedback control of evoked transmitter release (Glavinovic, 1979a;Magleby et al, 1981;Wessler et al, 1986;Matzner et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…It seems most likely that the remarkable effect reported by Das et al (1978) is an artefact arising from reliance on bioassay for measurement of ACh. While bioassay has proved a reliable method for ACh measurement in many circumstances, it is open to question on the grounds of specificity, especially when other drugs are used in the experiment.…”
mentioning
confidence: 99%
“…Discussion There is evidence that oxotremorine and other muscarinic agents inhibit the release of ACh in brain slices (Polak, 1971) and synaptosomes (Weiler & Jenden, 1977), myenteric plexus (Kilbinger & Wagner, 1975) and ciliary ganglion (Johnson, Beach, Alanis & Pilar, 1977), but apparently not from the perfused superior cervical ganglion of the cat (Kato, Collier, Ilson & Wright, 1975). In contrast, oxotremorine has been reported to produce a substantial increase in resting and stimulation-induced release from the rat phrenic nerve-diaphragm preparation (Das et al, 1978). Das and his colleagues (1978), using the dorsal muscle of the leech to bioassay ACh, reported that in the presence of 10 gM oxotremorine, the evoked (1 Hz) release of ACh rises to 1.3 nmol in 15 min, a value about 60 fold more than control.…”
mentioning
confidence: 99%
See 2 more Smart Citations